Geographical distribution of eight neuromuscular disorders in the Netherlands based on a nationwide registry - Johanna C.W. Deenen; André L.M. Verbeek; Pieter A. van Doorn; Catharina G. Faber; Anneke J. van der Kooi; Nicolette C. Notermans; Jan J.G.M. Verschuuren; Baziel G.M. van Engelen; Nicol C. Voermans (Rare)
Neuromuscular disorders are a very heterogeneous group of diseases and comprise a large number of patients. Epidemiological key figures on incidence, prevalence and mortality serve as basic information for individualised and public health care and researchers. Geographical mapping of the specific disorders is expected to provide valuable insights into clustering of the conditions, which points to possible environmental and genetical determinants. So far, mostly geographical maps of motor neuron diseases have been reported. By using record information from the Dutch nationwide Computer Registry of All Myopathies and Polyneuropathies (CRAMP) we aimed to generate geographical maps for eight disorders predominantly diagnosed in adults. We investigated the geographical distribution of newly diagnosed patients in the Netherlands from 2004 to 2011. The variables used were diagnosis, date of diagnosis, and the first two digits of the postal code for geographical location from CRAMP. The number of incident cases was divided by the total number of people populating the postal code area. Nationwide incidence maps were constructed for myotonic dystrophy, progressive (spinal) muscular atrophy, chronic inflammatory demyelinating polyneuropathy, facioscapulohumeral muscular dystrophy, inclusion body myositis, hereditary motor and sensory neuropathy, Pompe disease and oculopharyngeal muscular dystrophy. Considerable regional variation between disorders was observed, particularly for myotonic dystrophy and facioscapulohumeral muscular dystrophy. We provided the first neuromuscular atlas of the Netherlands with maps for eight disorders commonly seen in the neuromuscular practice. To address possible outliers due to low population numbers, Bayesian smoothing techniques should be considered in future research.